Engineering of porous bacterial cellulose toward human fibroblasts ingrowth for tissue engineering. Issue 22 (10th November 2014) - Hu, Yang; Catchmark, Jeffrey M.; Zhu, Yongjun; Abidi, Noureddine; Zhou, Xin; Wang, Jinhui; Liang, Nuanyi
Abstract